2018
DOI: 10.1016/s2214-109x(18)30397-8
|View full text |Cite|
|
Sign up to set email alerts
|

Feasibility and safety of mass drug coadministration with azithromycin and ivermectin for the control of neglected tropical diseases: a single-arm intervention trial

Abstract: SummaryBackgroundMass drug administration has made a major contribution to the public health control of several important neglected tropical diseases. For settings with more than one endemic disease, combined mass drug administration has potential practical advantages compared with separate programmes but needs confirmation of feasibility and safety. We undertook a study of mass drug administration in the Solomon Islands for trachoma and scabies control using ivermectin and azithromycin, key drugs in the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 31 publications
2
26
0
Order By: Relevance
“…Indeed, Streptococcal infection can subsequently result in rheumatic fever (and rheumatic heart disease) or post-streptococcal glomerulonephritis; both bacteria can also result in cellulitis and sepsis. Therefore, coadministration of oral antibiotics with topical and/or oral scabies therapy may be warranted [3,17,20].…”
mentioning
confidence: 99%
“…Indeed, Streptococcal infection can subsequently result in rheumatic fever (and rheumatic heart disease) or post-streptococcal glomerulonephritis; both bacteria can also result in cellulitis and sepsis. Therefore, coadministration of oral antibiotics with topical and/or oral scabies therapy may be warranted [3,17,20].…”
mentioning
confidence: 99%
“…In addition to the long-standing practice of co-administration with albendazole, large-scale studies have now demonstrated the safety of co-administration with azithromycin, opening the possibility of integrating control of scabies with control of yaws and/or trachoma. [128][129][130] Similarly, early analysis of a multi-national safety cohort study of combination therapy of ivermectin, diethylcarbamazine and albendazole (IDA) for lymphatic filariasis did not reveal safety concerns and administration of this combination of agents has now been recommended for specific epidemiological contexts within WHO guidelines. [131][132][133][134] Monitoring for development of resistance of mites to acaricides will also be important.…”
Section: Treatmentmentioning
confidence: 99%
“…A before-and-after study evaluated a single round of ivermectin-based MDA, offered to a population of 26,000, in combination with azithromycin MDA for trachoma control. The co-administration was well tolerated with no serious adverse events [ 36 ]. A smaller study, from a different region of the Solomon Islands, reported a reduction in scabies prevalence of greater than 90%, 12 months after ivermectin-based MDA [ 37 ].…”
Section: Community Controlmentioning
confidence: 99%
“…There are a number of opportunities for integration of scabies control with other NTDs, especially around the use of ivermectin [ 71 , 72 ]. Examples include successful co-mapping of scabies prevalence with other NTDs [ 17 , 73 ], and co-administration of ivermectin and azithromycin MDA with evaluation of multiple endpoints [ 36 , 37 ]. The roll-out of triple therapy (ivermectin, diethylcarbamazine, and albendazole) for the control of lymphatic filariasis [ 74 , 75 ] presents further opportunities to integrate evaluation of impact of this strategy on scabies.…”
Section: Outstanding Issuesmentioning
confidence: 99%